Children, Place and Sustainability - Somerville, Margaret. author. aut Link
XXV, 200 p.
Keywords: Through focusing on children's sustainability learning this book examines how school education can address the current environmental problems. It explores children's responses in literacy and language, arts-based approaches, and indigenous studies as well as scientific pedagogies to provide a unique insight into how children learn.